1987
DOI: 10.1128/jcm.25.1.142-145.1987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated in vitro transfer of Pasteurella haemolytica A1 on encapsulation, leukotoxin production, and virulence

Abstract: Pasteurella haemolytica serotype 1 was transferred daily for 128 serial passages on both unsupplemented brain heart infusion agar and the same basal medium supplemented with bovine blood, horse serum, and yeast extract. Repeatedly transferred cultures were shown to retain the ability to produce both capsular material and leukotoxin. Furthermore, intact organisms were found to be as toxic in vitro for bovine leukocytes and as virulent for mice as unpassaged cultures. These results indicate that the precaution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Stocks were plated on sheep blood agar and transferred weekly. Previous studies showed that multiple transfers do not affect leukotoxin production (13). For broth cultures, P. haemolytica was grown either in brain heart infusion broth or in Todd-Hewitt broth supplemented with 10 mM CaCl2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stocks were plated on sheep blood agar and transferred weekly. Previous studies showed that multiple transfers do not affect leukotoxin production (13). For broth cultures, P. haemolytica was grown either in brain heart infusion broth or in Todd-Hewitt broth supplemented with 10 mM CaCl2.…”
Section: Methodsmentioning
confidence: 99%
“…The determinants from serotypes 1, 2, and 11 were cloned into pBR322 on BamHI fragments of ca. 13 kbp. The determinant from serotype 3 was cloned into pBR322 on a ca.…”
Section: Methodsmentioning
confidence: 99%
“…The positive samples by the RT-PCR were subjected to blood agar culturing [8,9]. The colonies suggestive of Pasteurella were subjected to Gram-staining, catalase and oxidase test and growth on MacConkey agar for further identification [10].…”
Section: Bacterial Isolationmentioning
confidence: 99%
“…Pre-enrichment of nasal swabs in brain heart infusion (BHI) broth was performed immediately after sample collection and proceeded for incubation at 37 °C overnight according to Refs. [8,9]. Specimen…”
Section: Introduction mentioning
confidence: 99%